Penerapan Hukum Pelanggaran Integritas Akademik Terhadap Plagiarisme Hasil Karya Ilmiah dalam Upaya Pencegahan dan Penanggulangan Plagiat Pada Perguruan Tinggi - Mardayanti, Imelda; Arfah, Yenni (Community Service Progress, 2024)
Plagiarism is an act intentionally or unintentionally in obtaining or trying to obtain credit or value for a scientific work, by quoting part or all of another party's scientific works and/or works that are recognized as scientific works, without stating the source accurately and adequately. In practice, although some have received sanctions, however, there is no uniformity in determining plagiarism, so each university has its own policy. The problem in this research is how is law enforcement against plagiarism of scientific work as an effort to prevent and deal with plagiarism in universities? The research method used is normative juridical. The results of the research show that law enforcement against plagiarism of scientific work as an effort to prevent and deal with plagiarism in tertiary institutions has not been implemented properly. This is due to multiple interpretations of Article 10 paragraph (3) of the Regulation of the Minister of Education, Culture, Research and Technology Number 39 of 2021 concerning Academic Integrity in Producing Scientific Work, due to the indecisiveness of the phrase "partially", thus making universities in Indonesia ultimately has its own policy related to scientific writing that can be categorized as plagiarism.